ALK Rearrangement–Positive Pancreatic Cancer with Brain Metastasis Has Remarkable Response to ALK Inhibitors: A Case Report - Ou, Kai; Liu, Xiu; Li, Weihua; Yang, Yi; Ying, Jianming; Yang, Lin (Frontiers in Oncology, 2021)
Patients with metastatic pancreatic cancer typically have poor prognosis due to the limited effectiveness of existing treatment options. ALK rearrangement–positive is rare in pancreatic cancer, but may occur in those with KRAS-wild type. We present a 34-year-old young man with ALK rearrangement–positive and KRAS-wild pancreatic cancer who had a remarkable response to crizotinib after resistance to prior chemotherapy and re-response to alectinib after brain metastases developed. This clinical observation suggests that comprehensive molecular profiling to guide targeted therapies is not only feasible, but also significantly improves survival outcomes for a subgroup of patients with pancreatic cancer.